An overview of affirmative action policies in public federal universities in southeastern Brazil - Silva, Guilherme Henrique Gomes da (2019)
The theme of this paper is related to the access to and permanence of students from underrepresented groups in Brazilian Higher Education. Its objective is to provide a broad framework regarding the treatment of affirmative action policies in federal universities in the southeastern of Brazil. In this work, a broad and varied repertoire of official documents of all the nineteen federal universities of this Brazilian region was analyzed. After data analyses, three categories were constructed: admission, post-admission support, and pedagogical programs of retention. This study indicates that a broader understanding of affirmative action treatment can be an important point to achieve their goals, especially regarding the retention of the benefited students.